A cross-sectional survey of cadmium biomarkers and cigarette smoking. (3rd July 2016) - Hecht, Eric M.; Arheart, Kris; Lee, David J.; Hennekens, Charles H.; Hlaing, WayWay M.
Abstract: Cadmium contamination of tobacco may contribute to the health hazards of cigarette smoking. The 2005–2012 United States National Health and Nutrition Examination Survey data provided a unique opportunity to conduct a cross-sectional survey of cadmium biomarkers and cigarette smoking. Among a sample of 6761 participants, we evaluated mean differences and correlations between cadmium biomarkers in the blood and urine and characteristics of never, former and current smokers. We found statistically significant differences in mean cadmium biomarker levels between never and former smokers as well as between never and current smokers. In current smokers, duration in years had a higher correlation coefficient with urinary than blood cadmium levels. In contrast, number of cigarettes smoked per day had a higher correlation coefficient with blood than urinary cadmium levels. These data suggest that blood and urine cadmium biomarker levels differ by duration and dose. These findings should be considered in evaluating any association between cadmium and smoking related diseases, especially cardiovascular disease.